Indigenous-led precision public health: a new starting point - Baxter, Megan Fiona; Collins-Clinch, Amanda; Doxzen, Kevin; Thomas, Yarlalu; Rind, Shahmir; O’Donnell, Vicki; Baynam, Gareth (Frontiers in Public Health, 2024)
Precision public healthcare has been applied to bring about positive change, narrowing the gap in healthcare inequity for Aboriginal peoples. Three such examples include the Mappa, Lyfe Languages, and Pilbra Faces projects, which were all developed through engagement and codesign with Indigenous Australians and each meet a distinct critical need. The Mappa project offers patients and healthcare providers with the necessary geographical information to navigate and maximally utilize available healthcare services. Lyfe Languages is a community driven translational tool that empowers indigenous languages in healthcare. The Pilbara Faces project aims to create a database of clinical measurements enabling better disease diagnosis and monitoring. These three projects have been integrated into a multi-faceted precision public health program, the Healthy Pilbara Project Initiative, acting synergistically to improve the lives of Aboriginal peoples living in Western Australia.